Online Social Gathering Service Firm Strategy - Chusnul Rofiah (Trunojoyo University of Madura, 2021)
This research is written on the background of how the strategy to market online social gathering services is behind the rise of online social gathering scams. With the postpositivist paradigm of a qualitative approach to case study design, it has been found that the marketing strategy for online social gathering services will survive if it is supported by the products offered, causing reactions and consumer interest to be noticed, owned, used or consumed so as to satisfy consumer wants and needs. The products offered by the owner to consumers also vary. The price offered by the owner of this online social gathering is in accordance with the get that consumers want to get, so that consumers choose the get the social gathering slot according to their wishes, the use of online media is more effective to reach wider consumers and offer their products. The owner of this online social gathering benefits in the form of having a relationship with many people and also benefits from holding an online social gathering, the most important finding of this research is to include the mandate in running an online social gathering service business.